Lietuvių kalbos garsynas Augusto Schleicherio „Litauische Grammatik“ - Bacevičiūtė, Rima (Baltistica, 2009)
LITHUANIAN SOUND SYSTEM IN THE AUGUST SCHLEICHER’S ‘LITAUISCHE GRAMMATIK’The article presents an overview of the phonetics chapter from the ‘Lithuanian Grammar’ (Litauische Grammatik) published in 1856 in Prague by the leading Indo-Europeanist August Schleicher.In this chapter, entitled ‘The Science of Speech Sounds’ (Lautlehre), the author has described the phonetic system of the Lithuanian dialect of the Eastern Prussian Highlanders: articulation of vowels, diphthongs and consonants; accentuation and the influence of accent on the quantity of vowels; vowel alternations in the root of the words and the main principles of the composition of sounds, i.e. hiatus, elision, variations of the word endings. Schleicher has also given a comprehensive description of the features of the Eastern Prussian dialects.Most of Schleicher’s propositions are valuable for modern phonetics. He managed to discern the subtle characteristics of sounds, to describe thoroughly sound distinctions and to understand the complexity of the phonetic system of the language which was a foreign language to him.The targeted phonological thinking is specific for Schleicher: when giving the examples of sounds usage he almost everywhere uses an unspecified method of minimal pairs and perceives the differential power of sounds.
Keywords: lietuvių kalba; garsynas